Celebridades, acontecimentos e valores na sociedade contemporânea - Simões, Paula Guimarães (2020)
This article seeks to discuss the presence of celebrities in the contemporary scene, considering the actions carried out in events that project them on the public scene and that reveal values ​​of the society. The theoretical framework articulates the notions of celebrities, values ​​and events. The corpus is composed of 18 selected events in an event analysis laboratory from two categories: events that deal with privacy and gender issues. The analysis reveals values-principle that underpin the actions of celebrities, as well as disputes that take place around the affections present in the celebrization of celebrities.